Review of side-channel privacy inference of Android mobile devices - Futian SHI; Jian MAO; Jianwei LIU (网络与信息安全学报)
Android side channels may leak users’sensitive information.The existing Android side-channel attacks were analyzed and classified according to the type of the privacy-sensitive information with their inference models.The mainstream privacy inference approaches were analyzed and the deployed scenarios of these attacks were summarized.In addition,the mechanisms were discussed to detect or suppress the side-channel-based attacks and disclosed their limitations.Finally,the potential directions of research on side-channel-based privacy inference in Android systems were proposed.